Efforts to Improve the Quality of Human Resources in Facing Global Competition in the Industrial Revolution Era 4.0 - Elli Sulistyaningsih (Journal of Legal and Cultural Analytics, 2022)
The role of human resources is affirmed in the outline of state policy that the essence of Indonesia's national development is to build a complete Indonesian nation and all Indonesian people. In addition, in the general pattern of long-term development II, it is also emphasized that the main goal of national development is to improve the quality of indonesian society and society. . In addition, in the general pattern of long-term development II, it is also emphasized that the main goal of national development is to improve the quality of indonesian society and society. Human resources are the driving force of the activities of a country, in which citizens are concerned that carrying out all state activities, such as political, economic and others.